Improving strain measurements at Tidal Station Vyhne, Central Slovakia: Technological modernization using a capacitive transducer - KUBA, Michal; FABO, Peter; BÓDI, Jozef; BEDNÁRIK, Martin; MENTES, Gyula; BRIMICH, Ladislav; DÉREROVÁ, Jana (Contributions to Geophysics and Geodesy, 2024)
The year 2024 marks the 40-th anniversary of observation of Earth tides at the tidal station of Vyhne, Central Slovakia. The station was established through an international scientific collaboration in 1984. Since then, it has monitored the geodynamical phenomena almost continuously. At the beginning, the station was equipped with an extensometer with an analogue photo-recorder. Later on, the extensometer was fitted with a new sensor unit based on the principle of a capacitive transducer. The subject of this paper is the design and construction of a new sensor for measuring subtle displacements in the Earth’s crust due to the action of tidal and tectonic forces. Similarly to the currently operating sensor, it is based on the simple principle of measuring voltage changes on a movable sensing electrode fastened to a quartz glass tube. However, compared to the previous analogue version, a solution using the contemporary possibilities of high computing power of a modern microcontroller as well as its integrated peripherals are employed. Measured values are stored in a flash memory in off-line mode. The device is ready for operation in on-line mode for remote data collection in real time, as well. The first recorded data indicate that the instrument is working correctly, successfully registering the tidal phenomena. However, a significantly longer measurement period is required to ensure its proper operation and to rule out any potential adverse effects. Parallel measurements are to be carried out using both the new and former sensors, and the consistency of the results shall be examined.